Regression of plaque burden after primary percutaneous coronary intervention (PCI) in a patient with TVD: 4 years follow-up - Islam, AHM W; Munwar, S; Talukder, S; Reza, AQM; Ahmed, T (Pulse, 2011)
Coronary Artery disease (CAD) is an important cause of mortality and morbidity in the developed world as well as in Bangladesh. Treatment of Acute Myocardial Infarction (AMI) patient either by Streptokinase (STK) or Primary Percutaneous Coronary Intervention (pPCI) has increased the survival outcome and reduced the mortality. Several studies have documented the significant beneficial role pPCI in terms of in-hospital survival outcome over thrombolysis. Our patient, who had Anterior MI in 2004 and his CAG revealed TVD. pPCI of the culprit mid LAD lesion with Bare Metal Stent (BMS) was done immediately after hospitalization. He was later referred for CABG, but decision postponed because of asymptomatic status. His re-look CAG on 20-02-2008 (i.e., 4 yrs after the original procedure), revealed patent LAD stent with the regression of atherosclerotic plaque in Ostio-Proximal LAD and proximal LCX. Our findings indicated that pPCI with rigid control of CAD risk factors and modification of lifestyle plays a key role in the regression of atherosclerotic plaque and maintenance of stent patency. DOI: http://dx.doi.org/10.3329/pulse.v4i1.6959 Pulse Vol.4 January 2010 p.22-25